2022
DOI: 10.3390/diagnostics12092194
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Thyroid Viscosity in Healthy Subjects Using Ultrasound Shear Wave Dispersion (Viscosity PLUS)

Abstract: Shear-wave elastography (SWE) is widely used in thyroid evaluation, but multiple factors influence thyroid stiffness. Estimating tissue viscosity may enhance the ultrasound diagnosis of thyroid diseases, along with the ultrasound (US) and the SWE assessment. In order to be able to detect diffuse thyroid disease by viscosity measurements, it is essential to firstly define the normal values of thyroid viscosity in healthy subjects. Currently there are no published data on thyroid viscosity measurements. This fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous studies 20,32 identified a moderate correlation between viscosity and elasticity in the thyroid and kidneys. However, our study provided more conclusive findings.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies 20,32 identified a moderate correlation between viscosity and elasticity in the thyroid and kidneys. However, our study provided more conclusive findings.…”
Section: Discussionmentioning
confidence: 91%
“…SWD indirectly reflects the degree of tissue viscoelasticity by directly measuring SWD slope values. SWD has been used in human liver 19 and thyroid 20 and animal muscle injury modeling 21 studies. However, SWD as an imaging technique is still in the early stages of exploration.…”
mentioning
confidence: 99%
“…As a first step in evaluating thyroid viscosity, the viscosity of normal thyroid tissue was previously evaluated recently by two studies. It was established to be around 2.42 ± 0.41 Pa·s in the first study, which evaluated 121 healthy subjects [ 13 ] and 2.63 ± 0.47 Pa·s in the second study on 85 healthy volunteers [ 14 ]. Both studies estimated thyroid viscosity using the Vi PLUS method provided by the SuperSonic device and a curvilinear probe.…”
Section: Discussionmentioning
confidence: 99%
“…The SuperSonic MACH30 machine by Hologic provides a 2D imaging mode called viscosity Plane-wave UltraSound (Vi PLUS), a novel tool that allows the visualization and measurement of tissue viscosity inside an area of interest selected by the operator and quantified in Pascal seconds (Pa·s) [ 11 , 12 ]. A range of values for normal thyroid tissue was previously established [ 13 , 14 ], but the technique was not yet used in patients with thyroid diseases. The aim of this study is to assess the diagnostic value of Vi PLUS in detecting autoimmune thyroiditis and its predictive value for hypothyroidism in patients with CAT.…”
Section: Introductionmentioning
confidence: 99%
“…The cutoff value for thyroid tissue elasticity obtained from real-time ultrasound elastography for diagnosing HT showed 96% sensitivity and 67% specificity in adults[ 91 ], as well as 97.4% sensitivity and 100% specificity in children[ 92 ]. Based on ultrasound 2D shear-wave elastography, thyroid stiffness measured by shear-wave dispersion performed somewhat better in diagnosing HT than thyroid viscosity measured by shear-wave dispersion[ 93 ]. Compared with conventional ultrasound examination, high-frequency ultrasonic elastography exhibited a significantly higher diagnostic accuracy of HT (sensitivity, 92.16%; specificity, 92.86%; NPV, 86.67%; PPV, 95.92%)[ 94 ].…”
Section: Ultrasonography Application In Aitdmentioning
confidence: 99%